Unfolding of Filipino school leadership experiences in Doha, Qatar / Kris Anne Del Rosario and Inero Valbuena Ancho - Del Rosario, Kris Anne; Ancho, Inero Valbuena (Universiti Teknologi MARA, 2020)
Due to internationalization, Qatar is hiring foreign educators and leaders to share expertise in their country. Filipinos are mostly hired as domestic helpers, yet there are also Filipino leaders in educational institutions that exist, particularly in the capital city Doha. The researchers find it significant to examine the experiences of Filipino teachers abroad, due to the rising number of educators and school leaders in Qatar. Romanowski et al. (2018) cited that there is a very few studies regarding principalship and diversity of educators notwithstanding the enormous knowledge of research that emphasize leadership in school and diversity of students. The study attempts to unfold the lived experiences of Filipino school managers in international schools in Doha, Qatar specifically with: 1) the experiences of Filipino school managers in terms of: (a) Planning; (b) Organizing; (c) Leading and (d) Controlling. 2) The challenges of being a school leader in international schools in Doha. Four (4) themes emerged from the study with subthemes that depicted the experiences and challenges of Filipino school leaders. Theme 1 explains the Filipino school leaders in complying with mandates and policies. Theme 2 discusses the Filipino school leaders in adapting with culture. Theme 3 defines the Filipino school leaders conforming with programs. Theme 4 depicts the Filipino school leaders in conforming with resources. The study is beneficial to the aspiring and current school leaders not only to Filipinos, but also to other nationalities interested in or are presently managing international schools in Doha.